Luck stories: stress-testing contingency and agency at the margins of post-war American literature. Issue 3 (16th March 2018) - Gordon, Robert S. C.
ABSTRACT: The article examines four mid-twentieth-century American works of literature that explore and tell stories with notions of luck. It argues that luck in these works is deployed as a means to 'stress-test' the possibilities and the resilience of human agency, in the face of the contingencies and uncertainties of the modern. Widely varying in form and genre, and in different ways flawed, neglected or marginal in their author's work or in literary history, each of the four sets a preternatural or reified force of luck at the heart of a destabilised or displaced vision of the world, and watches the tensions and contradictions that result. Several common motifs and concerns emerge, touching on fundamental issues at stake in twentieth-century (capitalist) modernity: questions of power and freedom, economies of property and fertility, the morality of family and fidelity, moral responsibility and the calculus of guilt, the singularity and multiplicity of the self and its interactions with temporality. The four texts are: Arthur Miller, The Man Who Had All the Luck (1944); Philip K. Dick, Solar Lottery (1954) and The Game-Players of Titan (1963); and Luke Rhinehart, The Dice Man (1971).